Internalisasi Nilai-Nilai Agama Islam dalam Mengembangkan Budaya Religius Kelas V.1 di Madrasah Ibtidaiyah Negeri (MIN) 4 Jombang - Nurul ‘Aini, Robi’ul Afif; Zamroji, Muhammad; Wafiroh, Nilatit Tarabiyatul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
Internalization of Islamic religious values through madrasah religious culture to learners aims so that students are knowledgeable, can imagine and apply according to Islamic teachings, so that it becomes a good personality later, Islamic values that include aqidah, shari’ah and morals. Madrasah religious culture is the way or mindest of behaving all members of the madrassa based on the values of Islamic religious values. Madrasah religious culture plays a very important role, namely internalizing the value of Islamic religious values of learners in developing the religious culture of mdrasah ibtidaiyah negeri (MIN) 4 Jombang. The concept of internalization of Islamic values in madrasah ibtidaiyah negeri 4 Jombang can create an alternative solutions to the internalization of Islamic values, in the form of madrasah religious culture. Contrasting Islamic values (ta’aruf, tolerance, please help, tasamuh, tawazun, family nature) and discipline in the form of outlook on life, behavior, attitude through uswatun hasanah or tauladan in religious culture in accordance with the vision and mission of madrasah ibtidaiyah negeri 4 Jombang. Internalization of Islamic values through the container of madrasah religious culture with the policy of madrasah leadership as a supportive factor and other supporters such as: places of worship, vast madrassa courtyards, loudspeakers.